The Influence of Visual Attention, Emotional Engagement, and Brand Familiarity on Purchase Intention: A Case Study of Starbucks Consumers in Indonesia - Etty Zuliawati Zed; Sesri Sellina; Tri Mulyani Kartini (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This research explores how what customers look at, how they feel, and how well they know the brand affect their decision to buy at Starbucks in Indonesia. Because there are more and more coffee shops competing, especially in cities, it's very important to know how customers react to things they see, feel, and think about. We used a numbers-based method, gathering information from 210 people using set questions, and then examined the data using a special statistical technique called Partial Least Squares Structural Equation Modeling (PLS-SEM). The data indicates that what customers focus on visually greatly influences their desire to buy, indicating that compelling visual elements such as product presentation, packaging, and store ambiance capture consumer focus and enhance their willingness to buy. Emotional engagement also demonstrates a strong influence, suggesting that consumers’ affective connection with Starbucks’ brand identity and experience significantly drives their purchasing decisions. Additionally, brand familiarity positively affects purchase intention by reinforcing trust and reducing uncertainty in consumer choices. The results underscore how crucial it is to combine methods that focus on what people see, how they feel, and what they think about a brand to influence what customers do. This study contributes both theoretically and practically by offering insights into how marketing strategies can be optimized to strengthen purchase intention in a highly competitive market such as Indonesia’s coffee industry.